Implementation of a QR Code-Based Attendance System for Congregational Prayer in Fostering a Culture of Discipline Among Students - Abdul Azis; Jasiah Jasiah; Atin Supriatin (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
This study aims to examine the implementation of a QR Code-based attendance system for congregational prayers in fostering a culture of discipline among students at a high school in West Kotawaringin Regency. The study employs a qualitative approach using a case study design. Data were collected through in-depth interviews with the principal, the vice principal for student affairs, Islamic Religious Education teachers, and students, and were supported by observations and documentation. The results of the study indicate that the implementation of the QR Code-based attendance system is capable of improving the effectiveness of student attendance tracking in a more accurate, transparent, and real-time manner. In addition to serving as an administrative tool, this system also contributes to enhancing student discipline, particularly in terms of punctuality, adherence to rules, and the development of a sense of responsibility. In the initial stages, student discipline was primarily influenced by digital monitoring, but it gradually evolved into a habit ingrained in daily life. The success of the program’s implementation is supported by the commitment of school leadership, teacher involvement in monitoring, and periodic evaluation of attendance data. The use of digital technology in school religious activities serves as an innovative strategy to strengthen school management and foster students’ disciplined character on an ongoing basis